How to write a data management plan ... - UiT The Arctic University Of Norway (Zenodo, 2023)
Course material for the webinar “How to write a data management plan”, part of a webinar series on research data management (RDM) organized by UiT The Arctic University of Norway. For more information, please visit: site.uit.no/rdmtraining ...